2019
DOI: 10.1371/journal.pone.0224608
|View full text |Cite
|
Sign up to set email alerts
|

One simple claudication question as first step in Peripheral Arterial Disease (PAD) screening: A meta-analysis of the association with reduced Ankle Brachial Index (ABI) in 27,945 subjects

Abstract: Purpose and methodsA meta-analysis using data from seven German population-based cohorts was performed by the German Epidemiological consortium of Peripheral Arterial Disease (GEPArD) to investigate whether one question about claudication is more efficient for PAD screening than established questionnaires. Claudication was defined on the basis of the answer to one question asking for pain in the leg during normal walking. This simple question was compared with established questionnaires, including the Edinburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…In this study, we did not nd any difference in mean values of oscillometric-and Doppler-ABIs between patients presenting with leg pain and those without leg pain. This is contrary to a meta-analysis of 27,945 patients from 7 studies that reported lower mean ABI in patients with leg pain 21 .…”
Section: Discussioncontrasting
confidence: 91%
“…In this study, we did not nd any difference in mean values of oscillometric-and Doppler-ABIs between patients presenting with leg pain and those without leg pain. This is contrary to a meta-analysis of 27,945 patients from 7 studies that reported lower mean ABI in patients with leg pain 21 .…”
Section: Discussioncontrasting
confidence: 91%
“…Therefore, besides walk tests, the WIQ is a practical, reliable, valid, and representative measure of the functional capability in patients with intermittent claudication; it is also an easily obtained indicator of the efficacy of revascularization procedures. 13,33…”
Section: Discussionmentioning
confidence: 99%
“…The variety and depth of both the recording of environmental factors and the pheno-and genotypic characterization of the subjects allow further investigation of important questions beyond the existing study results. Furthermore, through the use of highly standardized assessment and database tools, data of this study is still used in big national (e.g., Kieback et al 2019;Bächle et al 2018; De Las Heras Gala 2016) and international research cooperations (e.g., Locke et al 2015;McClelland et al 2015). Overall, many important results regarding environmental issues could be achieved (e.g., Lucht et al 2020;Kartschmit et al 2020;Orban et al 2017;Fuks et al 2016;Hoffmann et al 2015;Hertel et al 2010).…”
Section: Longitudinal Cohort Study Designmentioning
confidence: 99%